The Administrative Judiciary Reforms in Hungary - Barsi-Fodor, Bea Éva (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
<span style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The study deals with the reforms of the administrative judiciary in Hungary from the 1880s to the present day. The main part of the considerations is the analysis of the first Hungarian codification of administrative court proceedings – Act No. I<span class="x-nobreak" style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> <span style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">of 2017 on administrative court proceedings, which is the result of only partially implemented intention of the legislator aimed at creating an administrative judiciary separate from the common judiciary, equipped with its own procedure and institutions. These plans have not been fully implemented to this day – judicial control of the administration (both before and now) has remained in the hands of common courts, and the 2017 Act retained the status of an act only partially independent of the Code of Civil Procedure, as in many the procedural law, the act refers to the provisions of the Code of Civil Procedure. Currently, judicial control of administration in Hungary is exercised by courts of two instances: in the first instance, they are adjudicated by either provincial courts by administrative chambers or, in cases provided for by law, by the Curia. The Curia adjudicates in second instance and on all matters of revision.